FACTORS ASSOCIATED WITH DEPRESSION AMONG ADOLESCENTS, ENROLLED IN EDUCATIONAL SETTINGS (AGE 15-19 YEARS) FROM A LOCALITY OF KARACHI, PAKISTAN - Maria Kanwal; Raja Khetpal; Ramna Shafique; Saleha Haider; Perah Ali; Rafay Shahab Ansari (Baqai Journal of Health Sciences, 2024)
Background: Depression is a prevalent and debilitating mental health issue among adolescents. This study aims to investigate the various factors associated with depression among adolescents, enrolled in educational settings aged 15 to 19 in Karachi, Pakistan.